Environment-friendly air purification gypsum and preparation method thereof

Through the combination of gypsum matrix and nanomaterials, the problem of poor performance of traditional air purification gypsum materials in purifying complex pollutants is solved, and efficient and stable air purification effects are achieved.

CN120607395APending Publication Date: 2025-09-09SHANDONG YOULEBANG BUILDING MATERIALS TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510716147.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-09-09

AI Technical Summary

Technical Problem

Traditional air purification gypsum materials are not effective in purifying complex pollutants such as volatile organic compounds and nitrogen oxides, and the preparation process lacks fine control, resulting in unstable material performance and low purification efficiency.

Method used

By combining gypsum matrix with functional materials such as nano-titanium dioxide, functionalized activated carbon, nitrogen-doped nano-silica, nano-zinc oxide and layered double hydroxide, high-efficiency air-purifying gypsum is formed through fine-tuning of particle size, doping concentration and process treatment.

Benefits of technology

It significantly improves the purification efficiency of volatile organic compounds and nitrogen oxides, material stability and durability, and solves the shortcomings of traditional gypsum materials in the treatment of complex air pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120607395A_ABST
    Figure CN120607395A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of air purification, and discloses environment-friendly air purification gypsum and a preparation method thereof.The environment-friendly air purification gypsum is prepared from, by mass, 60-70% of gypsum matrix, 5-10% of nano titanium dioxide, 10-20% of functional activated carbon, 3-5% of nitrogen-doped nano silicon dioxide and 5-8% of nano zinc oxide. By adopting the technical scheme that the gypsum matrix is combined with various functional materials, the effect of providing efficient air purification performance is achieved. Through the adsorption effect of the gypsum matrix and the synergistic effect of the nano titanium dioxide, the functionalized activated carbon and other materials, various harmful gases and pollutants can be removed at the same time, and the technical scheme that the gypsum matrix is combined with various functional materials is adopted, so that the effect of providing efficient air purification performance is achieved; through the adsorption effect of the gypsum matrix and the synergistic effect of the nano titanium dioxide, the functionalized activated carbon and other materials, various harmful gases and pollutants can be removed at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of air purification, in particular to an environmentally friendly air purification gypsum and a preparation method thereof. Background Art

[0002] With the advancement of industrialization, air pollution has become more and more serious, especially indoor air pollution has become one of the important factors affecting human health. Traditional air purification technologies mainly rely on activated carbon, photocatalysts, filters, etc., but these methods still have certain shortcomings. Although single activated carbon materials have good adsorption properties, they are not very effective in treating certain specific pollutants such as nitrogen oxides (NO X ) and volatile organic compounds (VOCs); photocatalysts (such as titanium dioxide) can decompose organic matter, but their photocatalytic performance is limited by the light source in indoor environments, and the catalytic effect is poor under visible light. Most air purification materials in the existing technology often have problems such as easy aging of materials and short-term effects when removing pollutants from the air.

[0003] Research on traditional air-purifying gypsum materials has largely focused on their function as building materials, but their application in air purification is relatively limited. While existing air-purifying gypsum materials can adsorb and remove air pollutants to a certain extent, their purification effect is not as good as that of specialized air-purifying materials. Generally, air-purifying gypsum relies only on its porous structure to absorb some odors and moisture, and is unable to specifically treat more complex pollutants such as volatile organic compounds and nitrogen oxides. This is due to the significant limitations of traditional gypsum-based materials in catalytic performance and adsorption capacity, making it difficult to meet the growing demand for air purification.

[0004] The preparation process of most air purification gypsums in the existing technology is relatively simple, and usually lacks fine control of the materials. In particular, when adding functional materials, the particle size, doping concentration and distribution are often not effectively controlled. This makes the performance of the material unstable, the purification effect is easily affected by environmental factors, and it is impossible to maintain a high purification efficiency for a long time. Summary of the Invention

[0005] In view of the shortcomings of the existing technology, the present invention provides an environmentally friendly air-purifying gypsum and a preparation method thereof, which solves the problem that most research on traditional air-purifying gypsum materials focuses on their function as building materials, but their application in air purification is relatively limited.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: an environmentally friendly air-purifying gypsum, comprising the following components in proportion by mass: Gypsum matrix 60-70%, Nano titanium dioxide 5-10%, Functionalized activated carbon 10-20%, Nitrogen doped nano-silicon dioxide 3-5%, Nano zinc oxide 5-8%, Layered double hydroxide 3-5%.

[0007] Furthermore, the gypsum matrix provides good structural support and adsorption, while functional materials such as nano-titanium dioxide, functionalized activated carbon, nitrogen-doped nano-silica, nano-zinc oxide and layered double hydroxide jointly play an air purification role through their respective catalytic, adsorption and antibacterial mechanisms. The mass ratio of calcium and sulfur in the gypsum matrix is ​​1:1, which helps to enhance the stability and adsorption performance of the material. The photocatalytic effect of nano-titanium dioxide and nano-zinc oxide can decompose harmful gases, and the surface nitridation treatment of activated carbon enhances the absorption of specific gases such as NO. X adsorption performance.

[0008] Preferably, the gypsum matrix is ​​a calcium sulfate mineral, the main component of which is calcium sulfate dihydrate, and in the gypsum matrix, the mass ratio of calcium to sulfur is 1:1. As the basic structural material of air purification gypsum, the nano-titanium dioxide has a particle size of 10 to 50 nanometers and is a copper-doped or iron-doped composite material with a mass fraction of 0.5 to 5%.

[0009] Furthermore, the calcium sulfate dihydrate in the gypsum matrix provides structural stability for the gypsum matrix and can absorb moisture and some harmful gases in the air. The mass ratio of calcium to sulfur is 1:1, which further ensures its stability. Nano-titanium dioxide has strong photocatalytic properties. The copper-doped or iron-doped composite material enhances its absorption capacity for visible light and enhances its absorption capacity for harmful substances (such as VOCs, NO) under ultraviolet and visible light. X The degradation ability of pollutants (such as pollutants) is improved, thereby improving the purification effect.

[0010] Preferably, the functionalized activated carbon is obtained by nitrogen doping treatment and has a particle size of 0.2 to 1.5 mm.

[0011] Furthermore, the surface nitridation treatment of functionalized activated carbon introduces nitrogen groups (such as amino, pyrrolyl, etc.), which not only increases the polarity of the surface, but also improves the selective adsorption capacity of activated carbon for harmful gases. The nitrogen-doped activated carbon has a higher adsorption capacity for NO X The gas has a higher adsorption efficiency and improves the air purification effect through its large number of pore structures.

[0012] Preferably, the nitrogen-doped nano-silica is prepared by a hydrothermal method.

[0013] Furthermore, nitrogen-doped nanosilica, prepared via a hydrothermal method, can evenly incorporate nitrogen into the silicon material, forming nitrogen-containing active sites. Nitrogen doping enhances its surface hydrophilicity and lipophilicity, improving its gas adsorption and catalytic capabilities, particularly in removing toxic gases such as formaldehyde and ammonia.

[0014] Preferably, the layered double hydroxide is calcium aluminum layered double hydroxide.

[0015] Furthermore, calcium aluminum layered double hydroxide (LDH) has a unique layered structure and high specific surface area, which can effectively adsorb harmful gases and heavy metal ions in the air. Its loading capacity enables it to capture pollutants in the air during the air purification process and effectively release clean gases, thereby improving the air purification effect.

[0016] A method for preparing environmentally friendly air-purifying gypsum comprises the following steps: Prepare a gypsum matrix and other functional materials mentioned in right 1, namely activated carbon, nano-titanium dioxide, nitrogen-doped nano-silica, nano-zinc oxide and layered double hydroxide; Pre-treatment of activated carbon, nano-titanium dioxide, nitrogen-doped nano-silicon dioxide, nano-zinc oxide and layered double hydroxide, including: The activated carbon is subjected to nitriding treatment to increase its surface nitrogen content; Nano-titanium dioxide is synthesized by sol-gel method, and the particle size is controlled to be 10 to 50 nanometers; The nitrogen-doped nano-silica was prepared by a hydrothermal method, with the nitrogen doping concentration being 5% to 10%; The gypsum matrix and the pre-treated functional material are mixed evenly according to the mass proportion to form a slurry; The slurry is molded and solidified to obtain environmentally friendly air-purifying gypsum.

[0017] Furthermore, the pre-treatment step optimizes the structure and performance of various functional materials through processes such as nitridation, sol-gel method and hydrothermal method, so that their activity in air purification can be fully exerted. Through these treatment methods, the particle size, doping concentration and morphology of the nanomaterials can be precisely controlled to improve their catalytic, adsorption and decomposition capabilities. The molding and curing steps ensure the uniform distribution of the gypsum matrix and various functional materials through reasonable process conditions, thereby improving the performance and stability of the final product.

[0018] Preferably, the pre-treatment step comprises: The activated carbon is subjected to nitriding treatment to increase the nitrogen content on its surface. The nitriding temperature is 400-800°C, the nitrogen source is ammonia, and the treatment time is 2-4 hours. Nano-titanium dioxide is synthesized by sol-gel method, and the particle size is controlled to be 10 to 50 nanometers; Nitrogen-doped nano-silica is prepared by a hydrothermal method, with a nitrogen doping concentration of 5% to 10%, a reaction temperature of 180 to 220° C., a reaction time of 6 to 12 hours, and ammonia as a nitrogen source.

[0019] Furthermore, during the nitridation treatment, the increase in nitrogen content on the surface of activated carbon significantly enhanced its adsorption capacity for specific harmful gases. In particular, the precise control of the nitridation temperature, nitrogen source and treatment time can optimize the nitridation effect. The sol-gel method and hydrothermal method, by controlling the reaction conditions, finely regulate the crystal structure and nitrogen doping concentration of nano-titanium dioxide and nitrogen-doped nano-silica to ensure their optimal catalytic activity.

[0020] Preferably, the molding step is to pour the slurry into a mold, let it stand for 1 hour, and cure it at 25-30° C. for 24-48 hours.

[0021] Furthermore, the standing and curing steps ensure the uniform distribution and sufficient reaction of the various components in the slurry. This process helps to form a stable gypsum structure and ensure the ultimate strength and performance of the air purification gypsum. The precise control of temperature and curing time avoids over-drying or over-hardening of the gypsum material, ensuring the quality and performance of the final product.

[0022] Preferably, the humidity in the curing step is controlled at 70-80%.

[0023] Furthermore, controlling the humidity at 70-80% helps ensure that the gypsum material has appropriate moisture content during the curing process, avoiding cracks or structural instability caused by over-drying, thereby ensuring the uniformity and long-term stability of the gypsum material.

[0024] Preferably, the drying step is performed at a temperature of 40 to 50° C. for 12 to 24 hours.

[0025] Furthermore, drying at 40-50°C effectively removes excess moisture from the gypsum, ensuring the hardness and strength of the gypsum material while avoiding deformation or performance degradation of the gypsum matrix caused by excessively high temperatures. By controlling the drying time and temperature, the stability and workability of the final product are ensured.

[0026] The present invention provides an environmentally friendly air-purifying gypsum and a preparation method thereof. It has the following beneficial effects: 1. This invention utilizes a gypsum matrix combined with a variety of functional materials to achieve highly effective air purification. Through the adsorption of the gypsum matrix and the synergistic effects of materials such as nano-titanium dioxide and functionalized activated carbon, the invention can simultaneously remove multiple harmful gases and pollutants. Compared to the existing use of a single material, this invention significantly improves air purification efficiency, resolving the problem of insufficient purification effects of a single material.

[0027] 2. The present invention adopts multiple pre-treatment technologies such as nitrogen doping and sol-gel method to achieve the performance improvement of various functional materials. By performing special treatment on activated carbon and nano-titanium dioxide, their adsorption and catalytic activities are significantly enhanced. Compared with traditional treatment methods, the treatment process of the present invention is more refined and effectively avoids the problem of insufficient or uneven material performance in traditional methods.

[0028] 3. The present invention ensures the stability and good dispersibility of the formula by controlling the proportion and particle size of each component. The particle size of nano titanium dioxide is controlled at 10 to 50 nanometers, which can optimize the photocatalytic effect. Compared with the materials with uneven particle sizes commonly found in the prior art, the present invention enables each component to exert its maximum efficiency, effectively avoiding the problems of uneven formula or low efficiency.

[0029] 4. The present invention includes precise curing and drying control, which ensures a tighter combination of the gypsum matrix and the functional materials, and higher stability and strength of the final product. Unlike the multiple curing or irregular drying processes in the prior art, the present invention solves the problems of cracks and deformation that are prone to occur in the existing preparation process by strictly controlling humidity and temperature, significantly improving the durability and service life of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Flow chart of the method of the present invention. DETAILED DESCRIPTION

[0031] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the drawings in the present specification. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0032] Please see the attached Figure 1 : Example 1: Preparation of environmentally friendly air-purifying gypsum Step 1: Prepare the raw materials Gypsum matrix: calcium sulfate dihydrate 60%.

[0033] Nano-titanium dioxide: 5%, particle size controlled at 30 nanometers, iron-doped composite material.

[0034] Functionalized activated carbon: 12%, particle size 1 mm, nitriding treatment to improve adsorption capacity.

[0035] Nitrogen-doped nano-silica: 4%, nitrogen doping concentration is 7%.

[0036] Nano zinc oxide: 6%, particle size is 20 nanometers.

[0037] Calcium aluminum layered double hydroxide: 5%.

[0038] Step 2: Pre-processing Activated carbon nitriding treatment: The functionalized activated carbon is placed in a nitrogen atmosphere, the temperature is controlled at 500°C, and the treatment time is 3 hours, so that the nitrogen content on its surface is significantly increased.

[0039] Nano-titanium dioxide synthesis: Nano-titanium dioxide was synthesized using the sol-gel method by mixing the precursor solution with the iron-doped material. The reaction temperature was maintained at 80 °C and the reaction time was 4 h.

[0040] Preparation of nitrogen-doped nano-silica: Synthesized by hydrothermal method, reaction temperature was 200°C, reaction time was 8 hours, nitrogen source was ammonia, and nitrogen doping concentration was ensured to be 7%.

[0041] Step 3: Ingredients and Mixing The gypsum matrix and the pre-treated functional materials are evenly mixed in a mass ratio to ensure that the gypsum and the activated carbon, nano-titanium dioxide, nitrogen-doped nano-silica and other components are evenly distributed. Mix them with a blender for 10 minutes to form a uniform slurry.

[0042] Step 4: Molding and curing The slurry was poured into a mold and allowed to stand for 30 minutes at 25°C for preliminary curing, and then placed in an environment at 30°C and 80% humidity for curing for 24 hours.

[0043] Step 5: Drying Dry at 40℃ for 12 hours to remove excess moisture and ensure product strength.

[0044] Final result This embodiment adopts a technical solution that combines a gypsum matrix with a variety of functional materials to achieve the effect of providing efficient air purification performance. Through the adsorption effect of the gypsum matrix and the synergistic effect of materials such as nano-titanium dioxide and functionalized activated carbon, the present invention can simultaneously remove multiple harmful gases and pollutants. Compared with the use of a single material in the prior art, the present invention can significantly improve the air purification efficiency and solve the problem of insufficient purification effect of a single material.

[0045] Example 2: Preparation of environmentally friendly air-purifying gypsum Step 1: Prepare the raw materials Gypsum matrix: calcium sulfate dihydrate 65%.

[0046] Nano titanium dioxide: 7%, particle size controlled at 40 nanometers, copper-doped composite material.

[0047] Functionalized activated carbon: 15%, particle size 0.5 mm, nitrided to improve its NO X adsorption capacity.

[0048] Nitrogen-doped nano-silica: 4%, nitrogen doping concentration is 9%.

[0049] Nano zinc oxide: 6%, particle size is 25 nanometers.

[0050] Calcium aluminum layered double hydroxide: 3%.

[0051] Step 2: Pre-processing Activated carbon nitriding treatment: Activated carbon is treated in a nitrogen environment at a temperature of 600°C for 3 hours to enhance its surface nitrogen groups and increase NO X adsorption performance.

[0052] Synthesis of nano-titanium dioxide: The titanium dioxide precursor solution was mixed with copper salt to carry out a sol-gel reaction. The reaction temperature was controlled at 90°C and the reaction time was 5 hours.

[0053] Preparation of nitrogen-doped nano-silica: hydrothermal synthesis, the temperature was set at 220° C., the reaction time was 10 hours, the nitrogen source was ammonia, and the nitrogen doping concentration was 9%.

[0054] Step 3: Ingredients and Mixing Mix all components uniformly according to mass ratio. Stir with a high-efficiency stirrer for 15 minutes to ensure that all ingredients are fully distributed and the slurry is completely uniform.

[0055] Step 4: Molding and curing Pour the slurry into the prepared mold and let it sit for 1 hour to ensure that the slurry is flat and stable. Then cure it at 30℃ and 75% humidity for 48 hours.

[0056] Step 5: Drying Drying is carried out for 18 hours at 50°C in a dry environment to remove moisture and ensure that the final product is strong and free of cracks.

[0057] Final result This embodiment utilizes a composite of nitrogen-doped nanomaterials and copper-doped titanium dioxide, resulting in a more robust photocatalytic effect, capable of decomposing harmful gases under low-light conditions. The uniform distribution of the gypsum matrix and other functional materials improves purification efficiency and addresses the limited photocatalytic effect and low gas removal efficiency seen in existing technologies.

[0058] Example 3: Preparation of environmentally friendly air-purifying gypsum Step 1: Prepare the raw materials Gypsum matrix: calcium sulfate dihydrate 70%.

[0059] Nano-titanium dioxide: 6%, particle size controlled at 25 nanometers, iron-doped composite material.

[0060] Functionalized activated carbon: 10%, particle size 1 mm, nitrided to improve its adsorption capacity for VOCs.

[0061] Nitrogen-doped nano-silica: 3%, nitrogen doping concentration is 6%.

[0062] Nano zinc oxide: 5%, particle size is 15 nanometers.

[0063] Calcium aluminum layered double hydroxide: 4%.

[0064] Step 2: Pre-processing Activated carbon nitridation treatment: Place the activated carbon in nitrogen at a temperature of 550°C for 2 hours to improve its ability to adsorb VOCs.

[0065] Synthesis of nano-titanium dioxide: Iron-doped nano-titanium dioxide was synthesized by sol-gel method with reaction temperature of 80°C and reaction time of 3 hours.

[0066] Preparation of nitrogen-doped nano-silica: The nitrogen doping concentration was set to 6%, and the synthesis was carried out by hydrothermal method with a reaction temperature of 180° C. and a reaction time of 6 hours.

[0067] Step 3: Ingredients and Mixing Mix the gypsum matrix with the functional materials in the correct proportions. Use a powerful agitator to mix for 10 minutes to ensure that each component is evenly distributed.

[0068] Step 4: Molding and curing Pour the slurry into the mold and let it stand for 1 hour to ensure that the slurry is uniform and does not flow, then cure it at 25-30℃ for 36 hours.

[0069] Step 5: Drying Dry at 45°C for 16 hours to remove excess moisture and ensure the hardness and stability of the plaster.

[0070] Final result This embodiment utilizes a combination of nano-titanium dioxide, activated carbon, and nitrogen-doped nano-silica to efficiently remove pollutants such as VOCs and formaldehyde, and significantly degrades nitrogen oxides in the air. Compared to existing technologies, the precise particle size control and nitrogen doping techniques significantly enhance the material's adsorption capacity and catalytic activity, resolving the problem of poor purification effectiveness found in existing technologies.

[0071] Example 4: Preparation of environmentally friendly air-purifying gypsum Step 1: Prepare the raw materials Gypsum matrix: calcium sulfate dihydrate 68%.

[0072] Nano titanium dioxide: 8%, particle size controlled at 20 nanometers, iron-doped composite material.

[0073] Functionalized activated carbon: 12%, particle size 0.8 mm, nitriding treatment to enhance its adsorption capacity for nitrogen oxides.

[0074] Nitrogen-doped nano-silica: 4%, nitrogen doping concentration is 8%.

[0075] Nano zinc oxide: 5%, particle size is 18 nanometers.

[0076] Calcium aluminum layered double hydroxide: 3%.

[0077] Step 2: Pre-processing Activated carbon nitriding treatment: Place the activated carbon in a nitrogen environment at a temperature of 550°C for 4 hours.

[0078] Nano-titanium dioxide synthesis: Iron-doped nano-titanium dioxide was synthesized by sol-gel method at a temperature of 85 °C and a reaction duration of 5 hours.

[0079] Preparation of nitrogen-doped nano-silica: A hydrothermal method was used, with a reaction temperature of 200° C., a nitrogen doping concentration of 8%, and a reaction time of 8 hours.

[0080] Step 3: Ingredients and Mixing Mix all the ingredients in proportion by weight and use a blender to mix for 12 minutes to ensure that each ingredient is evenly distributed.

[0081] Step 4: Molding and curing Pour the slurry into the mold and let it stand for 1 hour to ensure that the slurry is uniform and does not flow. Curing is carried out at 30℃ for 48 hours.

[0082] Step 5: Drying Place the gypsum material in a dry environment at a temperature of 45°C and dry it for 24 hours.

[0083] Final result This embodiment utilizes the powerful combination of nitrogen-doped nano-silica, iron-doped nano-titanium dioxide and functionalized activated carbon to enhance the adsorption capacity of nitrogen oxides and achieve photocatalytic degradation under lower light conditions. Compared with the existing technology, this invention provides stronger and longer-lasting purification capabilities and is particularly suitable for highly polluted environments.

[0084] Comparative Example 1: Gypsum-based air purification material without nano-modified materials Step 1: Prepare the raw materials Gypsum matrix: 90%.

[0085] Functionalized activated carbon: 10%, particle size 1 mm.

[0086] Step 2: Ingredients and Mixing Gypsum and activated carbon were mixed in proportion and stirred evenly. Since no nanomaterials were used, the overall mixing time was 5 minutes.

[0087] Step 3: Molding and curing The slurry was poured into the mold, allowed to stand for 1 hour, and then cured for 24 hours in an environment of 30°C and 80% humidity.

[0088] Step 4: Drying Dry at 40℃ for 12 hours to remove excess moisture.

[0089] Differences Air purification relies solely on the physical adsorption of gypsum, without using nanomaterials to enhance catalytic degradation capabilities.

[0090] Failure to use high-efficiency catalysts such as nano-titanium dioxide, nano-zinc oxide, and nitrogen-doped nano-silica may result in a lower decomposition rate of pollutants.

[0091] Applicable to low pollution environment, but for complex air pollutants (such as NO X The removal effect of VOCs may be poor, and there may be adsorption saturation problems after long-term use.

[0092] Comparative Example 2: Air Purification Gypsum without Activated Carbon Nitriding Treatment Step 1: Prepare the raw materials Gypsum matrix: 65%.

[0093] Nano titanium dioxide: 7%, particle size 40 nanometers, copper-doped composite material.

[0094] Functionalized activated carbon: 15%, particle size 0.5 mm, not nitrided.

[0095] Nitrogen-doped nano-silica: 4%, nitrogen doping concentration 9%.

[0096] Nano zinc oxide: 6%.

[0097] Calcium aluminum layered double hydroxide: 3%.

[0098] Step 2: Ingredients and Mixing The components were mixed and stirred for 10 minutes to form a homogeneous slurry.

[0099] Step 3: Molding and curing The slurry was poured into the mold, allowed to stand for 1 hour, and then cured for 48 hours in an environment of 30°C and 75% humidity.

[0100] Step 4: Drying Dry at 50°C for 18 hours.

[0101] Differences The activated carbon has not been nitrided, and no abundant nitrogen functional groups have been formed on its surface, which reduces its ability to absorb NO. X Chemical adsorption capacity of gases.

[0102] Activated carbon that has not been nitrided mainly relies on physical adsorption and is easily affected by humidity, which may reduce the efficiency of removing nitrogen oxides and VOCs.

[0103] The long-term purification capability of this formulation may be weak, especially when faced with complex gas mixtures, and its performance may not be as good as that of Example 2.

[0104] Comparative Example 3: Gypsum-based purification material without nitrogen-doped nanosilica Step 1: Prepare the raw materials Gypsum matrix: 70%.

[0105] Nano-titanium dioxide: 6%, particle size 25 nanometers, iron-doped composite material.

[0106] Functionalized activated carbon: 10%, particle size 1 mm, nitrogen treatment.

[0107] Nano zinc oxide: 5%, particle size 15 nanometers.

[0108] Calcium aluminum layered double hydroxide: 9%.

[0109] Step 2: Ingredients and Mixing Mix all ingredients in proportion and stir using a blender for 15 minutes.

[0110] Step 3: Molding and curing The mixed slurry was poured into a mold, allowed to stand for 1 hour, and then cured at 25-30°C for 36 hours.

[0111] Step 4: Drying Dry at 45°C for 16 hours to remove excess moisture and ensure product stability.

[0112] Differences The formula does not use nitrogen-doped nano-silica, which results in reduced catalytic activity of the overall material, especially the ability to degrade pollutants in low light or indoor environments may be limited.

[0113] Since nitrogen-doped nano-silica can improve the oxidative degradation ability of VOCs, this comparative example may not be effective in removing VOCs (such as formaldehyde, benzene, etc.).

[0114] It is suitable for general air purification needs, but in high-concentration pollution environments, its degradation rate may be slow and its purification capacity may be insufficient.

[0115] Comparative Example 4: Air Purification Gypsum without Iron-doped Nano-Titanium Dioxide Step 1: Prepare the raw materials Gypsum matrix: 68%.

[0116] Ordinary nano titanium dioxide: 8%, particle size 20 nanometers, undoped.

[0117] Functionalized activated carbon: 12%, particle size 0.8 mm, nitrogen treatment.

[0118] Nitrogen-doped nano-silica: 4%, nitrogen doping concentration 8%.

[0119] Nano zinc oxide: 5%, particle size 18 nanometers.

[0120] Calcium aluminum layered double hydroxide: 3%.

[0121] Step 2: Ingredients and Mixing Mix all the ingredients in proportion and stir with a blender for 10 minutes.

[0122] Step 3: Molding and curing The slurry was poured into the mold, left to stand for 1 hour, and cured at 30°C for 48 hours.

[0123] Step 4: Drying Place the product in a dry environment at 45°C and dry for 24 hours.

[0124] Differences This comparative example does not use iron-doped nano-titanium dioxide, but ordinary nano-titanium dioxide.

[0125] Iron-doped nano-titanium dioxide can improve its photocatalytic ability in weak light environments, while ordinary nano-titanium dioxide may have low activity in low light or indoor environments, resulting in a decrease in its ability to decompose pollutants.

[0126] It is suitable for environments with sufficient light, but at night or in dark conditions, the purification efficiency may drop significantly and perform worse than Example 4.

[0127] Comparative Example 5: Air Purification Gypsum Without Nano Zinc Oxide Step 1: Prepare the raw materials Gypsum matrix: 70%.

[0128] Nano-titanium dioxide: 6%, iron-doped composite material.

[0129] Functionalized activated carbon: 12%, nitrogenated.

[0130] Nitrogen-doped nanosilica: 4%.

[0131] Calcium aluminum layered double hydroxide: 8%.

[0132] Step 2: Ingredients and Mixing Mix all ingredients in proportion and stir using a blender for 15 minutes.

[0133] Step 3: Molding and curing The mixed slurry was poured into a mold, allowed to stand for 1 hour, and then cured at 30°C for 48 hours.

[0134] Step 4: Drying Dry at 45°C for 24 hours to remove excess moisture.

[0135] Differences The failure to use nano zinc oxide reduces the material's ability to inhibit microorganisms such as bacteria and mold, and its antibacterial properties may decrease.

[0136] Nano-zinc oxide usually has auxiliary photocatalytic function, and this formulation may perform poorly in photocatalytic degradation of organic matter.

[0137] It is suitable for environments with low antibacterial requirements, but its effect may be limited in places where clean air needs to be maintained for a long time (such as hospitals and laboratories).

[0138] Experiment 1: Air purification ability test (NO X Removal rate) Experimental Description This experiment is used to determine the effects of different air purification materials on nitrogen oxides (NO X ) removal effect in order to evaluate its air purification ability, two groups of experiments were selected for comparison: Example 2 (air purification material using nitrided activated carbon) vs. Comparative Example 2 (material without activated carbon nitridation) Example 4 (using iron-doped nano-titanium dioxide) vs. Comparative Example 4 (using ordinary nano-titanium dioxide) Experimental procedures Test environment preparation Choose a 1m 3 The sealed test chamber ensures no airflow interference.

[0139] Initial NO X The concentration was set at 500 ppb using a standard NO2 gas generator.

[0140] The temperature was set at 25°C and the humidity was 50%, controlled by a constant temperature and humidity device.

[0141] Sample preparation Select blocks of material that are 10cm x 10cm x 2cm, ensuring the same surface area.

[0142] Dry for 48 hours in advance to avoid moisture.

[0143] Experimental process After placing the sample, the test chamber is sealed and the photocatalytic purification process begins.

[0144] Using simulated sunlight (300W / m 2 ) for irradiation to simulate daily use environment.

[0145] Take samples every 30 minutes and record NO X The experiment lasted for 3 hours.

[0146] Data Analysis Calculate NO X Removal rate: ; in, Initial NO X concentration, is NO after time t X concentration.

[0147] Experimental data table Table 1: Different materials NO X Removal rate experimental data Experimental Summary The role of nitrided activated carbon in NO X The removal rate is particularly evident. X The removal rate was significantly lower than that of Example 2. The nitriding treatment increased the nitrogen functional groups on the surface of the activated carbon, which improved the removal of NO. X Chemical adsorption capacity of these nitrogen functional groups provides more electrons, promoting the reduction of NO2 into harmless N2, reducing NO XResidues in the air, while unnitrided activated carbon mainly relies on physical adsorption and is easily affected by humidity. The adsorption effect is good in a short time, but in the long run, saturation is faster, resulting in NO X The removal capacity is reduced.

[0148] The catalytic activity of iron-doped nano-titanium dioxide has also been verified. Example 4 is significantly better than Comparative Example 4. Iron doping promotes the separation of photogenerated electrons and holes, improves the photocatalytic efficiency, and makes NO X It is oxidized to NO3 faster. In contrast, ordinary nano-titanium dioxide performs poorly under low light conditions and is prone to electron-hole recombination, which affects the catalytic reaction rate. It is worth noting that within the first 60 minutes, the NO X The difference in removal rates is not particularly large, but after 90 minutes, the removal rate of Example 4 is significantly improved, which shows that the effect of iron doping is gradually reflected in the continuous purification process.

[0149] From the overall trend, the NO in Examples 2 and 4 X The removal ability is significantly better than that of the corresponding control example. The combination of photocatalysis and chemical adsorption makes NO X The conversion efficiency is higher, especially for long-term operation scenarios, the advantages of nitrided activated carbon and iron-doped nano-titanium dioxide will become more and more obvious. This enhancement mechanism is not only related to the surface modification of the material, but also involves the transition characteristics of electrons in the photocatalytic reaction and the distribution of surface adsorption sites.

[0150] Experiment 2: VOCs (formaldehyde) degradation test Experimental Description This experiment is used to test the ability of different materials to degrade formaldehyde, a common indoor volatile organic compound (VOCs). The core of the comparison lies in whether they contain nitrogen-doped nano-silica and whether nano-modification technology is used, and to observe their degradation performance under the same environment.

[0151] Experimental comparison groups: Example 3 (nitrogen-doped nanosilica) vs. Comparative Example 3 (non-nitrogen-doped nanosilica) Example 1 (using nano-modified materials) vs. Comparative Example 1 (not using nano-modified materials) Experimental procedures Environment Setup Test space: 0.5m 3 Glass-enclosed cabin reduces interference with air circulation.

[0152] Initial formaldehyde concentration: set to 2.0 mg / m 3 , using a standard formaldehyde gas generating device.

[0153] Temperature and humidity control: temperature 25℃, humidity 55%, stable experimental environment.

[0154] Sample preparation The preparation size of each material is 10 cm × 10 cm × 2 cm, and the exposed effective surface area is consistent.

[0155] Place in a constant temperature box for 48 hours to eliminate the influence of additional adsorption.

[0156] Experimental process After the formaldehyde release reaches a stable state, the test sample is placed in the glass chamber.

[0157] Using ultraviolet lamp (365nm, 50W / m 2 ) simulated photocatalytic conditions.

[0158] The formaldehyde detector takes samples and records the formaldehyde concentration every hour for 6 hours.

[0159] Experimental data table Table 2: Experimental data of formaldehyde degradation rate of different materials Experimental Summary The comparison of formaldehyde degradation ability is very intuitive. The degradation efficiency of Example 3 is much higher than that of Comparative Example 3. The role of nitrogen-doped nano-silica cannot be ignored. It not only provides higher photocatalytic activity, but also maintains stable catalytic efficiency throughout the degradation process. Under light, the nitrogen-doped sites enhance electron transitions, thereby improving the separation efficiency of photogenerated electron-hole pairs, which means that formaldehyde molecules are more easily decomposed into CO2 and H2O. The material of Comparative Example 3 has limited catalytic ability, a faster recombination rate of photogenerated electrons, and a lower degradation reaction efficiency.

[0160] On the other hand, the performance of Example 1 is also better than that of Comparative Example 1. The nano-modified material plays a synergistic role in many aspects, not only in photocatalysis, but also in the adsorption of formaldehyde molecules by the porous structure. The high specific surface area of ​​the material surface allows formaldehyde molecules to enter the catalytic zone faster, thereby increasing the degradation rate. Since Comparative Example 1 has no nano-modification, it can only rely on the physical adsorption capacity of gypsum itself, showing obvious hysteresis. Experimental data show that after 3 hours, the degradation rate of Example 1 remains high, while that of Comparative Example 1 has stabilized, indicating that its purification capacity is limited.

[0161] It is worth noting that during the experiment, the degradation rate of Comparative Example 3 was not too low in the first two hours, but then slowed down significantly. This may be related to the adsorption saturation point of the material. The catalytic efficiency of undoped nitrogen-doped silica itself is insufficient, and the reaction of photogenerated electrons on the surface is limited, resulting in a decrease in the reaction rate. However, due to the modification of the catalytic center, Example 3 maintained a faster degradation trend throughout the entire experimental process. This shows that the nitrogen doping strategy not only improves the initial catalytic ability of the material, but also enhances the stability of continuous degradation, making it more applicable.

[0162] Experiment 3: Antibacterial performance test (bacterial survival rate) Experimental Description This experiment mainly tests the antibacterial properties of different materials against Escherichia coli and Staphylococcus aureus. By comparing two purification materials with different modification methods, the difference in their antibacterial effects is analyzed to further verify the effects of nano-zinc oxide and iron-doped nano-titanium dioxide.

[0163] Experimental comparison groups: Example 4 (containing iron-doped nano-titanium dioxide) vs. Comparative Example 4 (ordinary nano-titanium dioxide) Example 5 (containing nano zinc oxide) vs. Comparative Example 5 (not containing nano zinc oxide) Experimental procedures Bacterial culture and environmental preparation Take Escherichia coli and Staphylococcus aureus strains and culture them in LB medium at 37℃ for 24 hours to ensure that the bacterial solution concentration reaches 10 6 CFU / mL (colony forming units).

[0164] Take a 5 cm × 5 cm material test piece and sterilize it by high pressure at 121 ° C for 30 minutes to eliminate background bacterial interference.

[0165] Bacterial inoculation and incubation 100 μL of bacterial solution was added to the surface of each material to ensure uniform distribution.

[0166] Place in an incubator with 80% humidity and incubate at 37°C for 24 hours.

[0167] A blank control group (no inoculated material) was set up.

[0168] Bacterial survival rate test After sampling, the bacteria were eluted in sterile PBS (phosphate buffered saline), diluted 10-fold, spread on LB agar medium, and cultured at 37°C for 24 hours before counting the colonies.

[0169] Calculate the inhibition rate: ; in, is the colony count of the control group, is the colony count of the sample group.

[0170] Experimental data table Table 3: Different materials 3 Experimental data on bacterial inhibition rate Experimental Summary The antibacterial effect of iron-doped nano-titanium dioxide far exceeds that of ordinary nano-titanium dioxide, especially in the Staphylococcus aureus experiment, the inhibition rate is close to 98%. This is easy to explain. Iron doping changes the band gap of titanium dioxide, making it still able to effectively catalyze the production of reactive oxygen species (ROS) under visible light. These ROS, especially hydroxyl radicals (OH) and superoxide anions (O2 -) , which can destroy cell walls, damage DNA, and ultimately lead to bacterial death. In contrast, Comparative Example 4 only relies on the photocatalytic ability of ultraviolet light excitation, resulting in limited production of active oxygen and an antibacterial effect that is significantly inferior to that of Example 4.

[0171] The effect of nano zinc oxide is also obvious. The survival rate of E. coli in Example 5 is much lower than that in Comparative Example 5. ZnO nanoparticles not only have good photocatalytic activity, but also can release Zn in aqueous solution. 2+ Ions, these ions can penetrate the bacterial cell membrane, bind to proteins, and disrupt their normal metabolism. 2+ The release rate is slow, which makes the antibacterial effect of the material more lasting. In the later stage of the experiment, even if the light intensity is reduced, Example 5 still shows a stable antibacterial effect, and the bacterial survival rate of the comparative example 5 group gradually recovers, indicating that its antibacterial ability mainly depends on the initial physical adsorption rather than the chemical sterilization mechanism.

[0172] It should be noted that although both exhibit good antibacterial effects, their mechanisms of action are different. Iron-doped titanium dioxide mainly relies on photocatalysis, while nano-zinc oxide combines a dual mechanism of photocatalysis and ion release. Therefore, in specific application scenarios, such as long-term exposure to light, nano-zinc oxide may be a better choice. In an environment assisted by ultraviolet or visible light, iron-doped titanium dioxide is more advantageous. This differentiated performance also provides direction for subsequent material optimization.

[0173] Experiment 4: Long-term stability test (performance decay rate) Experimental Description This experiment is used to evaluate the changes in purification effects of different materials after long-term use. Air purification materials must not only perform well in the initial stage, but also maintain high efficiency after long-term use. Therefore, through 30 consecutive days of testing, the material's NOX The attenuation of the removal effect is investigated and its stability is examined.

[0174] Experimental comparison groups: Example 2 (using nitrided activated carbon) vs. Comparative Example 2 (unnitrided activated carbon) Example 3 (nitrogen-doped nanosilica) vs. Comparative Example 3 (non-nitrogen-doped nanosilica) Experimental procedures Experimental environment preparation Choose 1m 3 The closed test chamber avoids the influence of external airflow.

[0175] Initial NO X The concentration was set at 500 ppb and a standard NO2 gas generator was used to maintain a constant input.

[0176] The temperature and humidity were controlled at 25℃, 50%RH to avoid environmental interference.

[0177] Sample preparation Select 10cm×10cm×2cm material blocks, 3 pieces per group, to ensure repeatability.

[0178] The samples were pre-treated for 48 hours to remove excess moisture and maintain a consistent state.

[0179] Long-term testing process Release NO regularly every day X , keeping the initial concentration constant.

[0180] Using 300W / m 2 Artificial light sources simulate natural photocatalytic environments.

[0181] Record NO every day X The removal rate was tested continuously for 30 days and the performance decay rate was calculated.

[0182] Data Calculation Calculate the removal rate: Calculate the performance decay rate: ; ; in, For the first day, NO X Removal rate, For the 30th day NO X Removal rate.

[0183] Experimental data table Table 4: NO after long-term use of different materials X Changes in removal rate Experimental Summary The long-term performance of nitrided activated carbon is significantly better than that of ordinary activated carbon. X The removal effect decays at a slow rate. The removal rate of Comparative Example 2 began to drop sharply on the 10th day and dropped to 50.3% after 30 days. This phenomenon is related to the adsorption saturation point of the material. The activated carbon without nitriding mainly uses physical adsorption. After the adsorption saturation, the effect decreases and it is difficult to continue working. The nitrogen functional groups on the surface of nitrided activated carbon enhance the chemical adsorption of NO2, making NO X It can effectively remove NO2 over a longer period of time. In addition, some NO2 can be catalytically reduced to harmless nitrogen, further reducing the cumulative effect. Therefore, the nitrided material not only works quickly but also maintains stable operation for a longer period of time.

[0184] The long-term stability of nitrogen-doped nano-silica is also good. The Example 3 group still maintained a removal rate of 71.8% after 30 days, while the comparative example 3 only had 53.9%. The key to this gap is that nitrogen doping improves the photocatalytic durability of the material. For nano-silica that is not doped with nitrogen, the photocatalytic sites may be passivated over time, resulting in a decrease in activity. However, nitrogen-doped silicon dioxide has an additional electron supply effect, which inhibits the recombination of photogenerated electrons and holes, making its catalytic performance relatively stable after long-term operation. This effect is particularly evident in low-light environments, which makes the material still have a high catalytic efficiency under weak indoor lighting conditions.

[0185] Looking at the overall trend, both Examples 2 and 3 exhibited significant resistance to degradation, while the corresponding comparative material showed a significant performance decline after 20 days. This not only illustrates the impact of surface modification on the long-term performance of the material, but also highlights the importance of the synergistic effect of catalysis and chemical adsorption. Future optimization directions may require further improving the durability of the photocatalytic sites, or combining other stabilizers to slow the catalyst's light degradation to achieve longer-term air purification effects.

[0186] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. An environmentally friendly air-purifying gypsum, characterized in that: It includes the following components in proportion by mass: Gypsum matrix 60-70%, Nano titanium dioxide 5-10%, Functionalized activated carbon 10-20%, Nitrogen doped nano-silicon dioxide 3-5%, Nano zinc oxide 5-8%, Layered double hydroxide 3-5%.

2. The environmentally friendly air-purifying gypsum according to claim 1, characterized in that: The gypsum matrix is ​​a calcium sulfate mineral, the main component of which is calcium sulfate dihydrate. In the gypsum matrix, the mass ratio of calcium to sulfur is 1:

1. As the basic structural material of air purification gypsum, the nano-titanium dioxide has a particle size of 10 to 50 nanometers and is a copper- or iron-doped composite material with a mass fraction of 0.5 to 5%.

3. The environmentally friendly air-purifying gypsum according to claim 1, characterized in that: The functionalized activated carbon is obtained through nitrogen doping treatment, and its particle size is 0.2 to 1.5 mm.

4. The environmentally friendly air-purifying gypsum according to claim 1, characterized in that: The nitrogen-doped nano-silica is prepared by a hydrothermal method.

5. The environmentally friendly air-purifying gypsum according to claim 1, characterized in that: The layered double hydroxide is calcium aluminum layered double hydroxide.

6. A method for preparing an environmentally friendly air-purifying gypsum, applied to the environmentally friendly air-purifying gypsum according to claims 1-5, characterized in that: The following steps are involved: Prepare a gypsum matrix and other functional materials mentioned in right 1, namely activated carbon, nano-titanium dioxide, nitrogen-doped nano-silica, nano-zinc oxide and layered double hydroxide; Pre-treatment of activated carbon, nano-titanium dioxide, nitrogen-doped nano-silicon dioxide, nano-zinc oxide and layered double hydroxide, including: The activated carbon is subjected to nitriding treatment to increase its surface nitrogen content; Nano-titanium dioxide is synthesized by sol-gel method, and the particle size is controlled to be 10 to 50 nanometers; The nitrogen-doped nano-silica is prepared by a hydrothermal method, with the nitrogen doping concentration being 5 to 10%; The gypsum matrix and the pre-treated functional material are mixed evenly according to the mass proportion to form a slurry; The slurry is molded and solidified to obtain environmentally friendly air-purifying gypsum.

7. The method for preparing an environmentally friendly air-purifying gypsum according to claim 6, characterized in that: The pre-treatment steps include: The activated carbon is subjected to nitriding treatment to increase the nitrogen content on its surface. The nitriding temperature is 400-800°C, the nitrogen source is ammonia, and the treatment time is 2-4 hours. Nano-titanium dioxide is synthesized by sol-gel method, and the particle size is controlled to be 10 to 50 nanometers; Nitrogen-doped nano-silica is prepared by a hydrothermal method, with a nitrogen doping concentration of 5% to 10%, a reaction temperature of 180 to 220° C., a reaction time of 6 to 12 hours, and ammonia as a nitrogen source.

8. The method for preparing an environmentally friendly air-purifying gypsum according to claim 6, characterized in that: The molding step comprises pouring the slurry into a mold, allowing it to stand for 1 hour, and curing it at 25-30° C. for 24-48 hours.

9. The method for preparing an environmentally friendly air-purifying gypsum according to claim 6, characterized in that: The humidity in the curing step is controlled at 70-80%.

10. The method for preparing an environmentally friendly air-purifying gypsum according to claim 6, characterized in that: The drying step is performed at a temperature of 40 to 50° C. for 12 to 24 hours.